2022
DOI: 10.3390/jcm11175096
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metabolism and Ischemia-Reperfusion Injury: Two Sides of the Same Coin

Abstract: Cancer cells are characterized by the reprogramming of certain cell metabolisms via activation of definite pathways and regulation of gene signaling. Ischemia-reperfusion injury (IRI) is characterized by tissue damage and death following a lack of perfusion and oxygenation. It is most commonly seen in the setting of organ transplantation. Interestingly, the microenvironments seen in cancer and ischemic tissues are quite similar, especially due to the hypoxic state that occurs in both. As a consequence, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…The most important mechanism is the inflammation-induced procoagulant pathway, which invariably leads to microthromboses and local ischemia [ 23 , 24 ]. Together with the acidic microenvironment and local ischemia, the peritumoral inflammation can have a detrimental effect on initial postoperative anabolic response phase, including anastomotic healing [ 25 , 26 , 27 ]. On the other hand, prolonged inflammation may impede local anastomotic healing by excessive mobilization of macrophages and lymphocytes, with subsequent secretion and regulation of proteases and matrix metalloproteinases, associated with a dysregulation in growth factor synthesis and impeded lymphoblastic migration and growth [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important mechanism is the inflammation-induced procoagulant pathway, which invariably leads to microthromboses and local ischemia [ 23 , 24 ]. Together with the acidic microenvironment and local ischemia, the peritumoral inflammation can have a detrimental effect on initial postoperative anabolic response phase, including anastomotic healing [ 25 , 26 , 27 ]. On the other hand, prolonged inflammation may impede local anastomotic healing by excessive mobilization of macrophages and lymphocytes, with subsequent secretion and regulation of proteases and matrix metalloproteinases, associated with a dysregulation in growth factor synthesis and impeded lymphoblastic migration and growth [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most important mechanism is the inflammation-induced procoagulant pathway, which invariably leads to microthromboses and local ischemia [23,24]. Together with the acidic microenvironment and local ischemia, the peritumoral inflammation can have a detrimental effect on initial postoperative anabolic response phase, including anastomotic healing [25][26][27].…”
Section:  Discussionmentioning
confidence: 99%
“…Hydrolytic enzymes, such as secreted aspartyl proteinases (SAPs), phospholipases (PLs) and Candida species play a role in the pathogenesis of VVC [ 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Numerous studies have reported that approximately 75% of women have experienced or been diagnosed with VVC [ 1 , 2 , 3 , 4 , 5 , 20 , 21 , 22 , 23 , 24 , 25 ]. The maximum incidence of this infection is at reproductive age, an aspect also observed in our study, the average age of the patients analyzed by us being between 27.88 years and 35.50 years.…”
Section: Discussionmentioning
confidence: 99%
“…Along with bacterial vaginosis, candidiasis is associated with symptoms such as pruritus, local irritation, dysuria, dyspareunia, and altered vaginal secretion, gritty/brownish white or local pain. This symptomatology can be supported and aggravated by the risk factors of this infection [ 2 , 4 , 25 , 26 , 27 , 28 , 29 , 30 ]. Poor hygienic conditions and lack of information and access to medical services can negatively influence the situation of patients diagnosed with this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation